El control del movimiento obrero como una necesidad del Estado de México (1917-1936) - Reyna, Manuel; Palomares, Laura; Cortez, Guadalupe (Revista Mexicana de Sociología, 2024)
El control del movimiento obrero como una necesidad del Estado de México (1917-1936).